MADRASAH LEADERSHIP IN BUILDING PUBLIC OPINION (Transformation from Conservative to Collaborative Approach) - Yakin, Ainul; Alfaridli, Muhammad Alfi; Lestari, Yusri Dwi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aims to analyze the transformation of madrasah leadership from a conservative approach to a collaborative one in building a more positive public opinion. The study was conducted at Madrasah Aliyah (MA) Darul Musthofa Tiris Probolinggo with a qualitative approach through case studies. Data were collected through in-depth interviews, participatory observations, and document analysis involving the head of the madrasah, teachers, students, parents, and the surrounding community. The results of the study indicate that the implementation of collaborative leadership in madrasahs has succeeded in improving communication between stakeholders and strengthening the relationship between the madrasah and the community. Through various communication channels such as social media, direct meetings, and digital announcements, information can be conveyed clearly and openly. In addition, the use of technology in communication accelerates the dissemination of information and increases active participation from all related parties. This study also found that the communicative and open leadership of the madrasah head plays an important role in creating a collaborative environment, as well as increasing public trust in the madrasah. This finding is in line with the theory of transformational leadership and effective communication, which emphasizes transparency, collaboration, and the use of technology in improving educational performance. This study contributes to developing a more inclusive and responsive madrasah leadership model to the needs of the times.